Institutional and Partisan Sources of Legislative Conflict: The Brazilian Case - Hiroi, Taeko; Rennó, Lucio (Revista Ibero-Americana de Estudos Legislativos, 2014)
We assess the effects of individual, partisan, and institutional dimensions of conflict on the duration and outcome of the legislative processes in the Brazilian Congress. Our analysis indicates that legislative approval is more likely when the size of the governing coalition is either relatively small or extremely large and least likely when the coalition size is barely over the supermajority threshold to approve constitutional amendments. In contrast, legislative rejection is less likely with either modestly sized coalitions or very large coalitions, but most likely when it is approximately the size of the supermajority threshold. We also find that the effects of certain institutional variables are time-variant. Bicameral incongruence initially has a positive effect on legislative approval but soon begins to yield negative effects, delaying bills’ passage. On the other hand, with the passage of time, executive proposals are less likely to be approved or rejected, although their initial effects are the opposite. Finally, preference heterogeneity among Brazilian deputies, which should have a significant impact if lawmaking were contingent upon individualistic politicians and weak parties unable to deliver bloc votes, has mixed effects: it has no statistically discernible impact on legislative passage. However, it has a delaying effect on proposal rejection.